Purification of L1-ribonucleoprotein particles (L1-RNPs) from cultured human cells - Mandal, Prabhat K. (Methods Mol Biol, 2016)
Almost two third of the human genome is repetitive DNA, mostly derived from different kinds of transposon and retrotransposon sequences. Although most of these sequences are stable in the genome, one class called Long INterpersed Element (LINE1 or L1) is actively jumping in the human genome, particularly in brain, germ cells and certain types of cancer. Recent estimates predict that L1 activity combined with L1-mediated activity is responsible for a new insertion in 1 out of 25 newborns. In humans, more than 100 single-gene disease cases have been reported due to L1 activity. An active L1 encodes two proteins designated as ORF1p and ORF2p. L1 jumps by a target primed reverse transcription (TPRT) mechanism where L1 RNA forms L1-RNPs after binding with L1 proteins. L1-RNPs then enter into the nucleus where L1 RNA is converted to cDNA at the site of integration which subsequently integrates into the genome with the help of the L1 proteins (ORF1p and ORF2p) and other cellular factors. Although L1 is continuously jumping in the human genome the basic mechanism and requirement of other cellular factors in L1 retrotransposition is relatively unknown due to the difficulty in purifying intact L1-RNPs. Here we describe a detailed protocol for purification of L1-RNPs by an immunoaffinity method.